Anales del Ministerio de Agricultura (Buenos Aires Argentina. Ministerio de Agricultura de la Nación)
Signatura: 63/18
Existencia: 1903- 1(2); 1904- 1(3-5, 8-9); 1904- 2(6), 3(1); 1905- 1(1); s.f.- 7(1)
Keywords: Argentina; Ganaderia; Agricultura